An Introduction to AdS/CFT Correspondence for Phenomenologists - 陈斌 (Communications in theoretical physics, 2011)
We give a brief introduction to the AdS/CFT correspondence and its application to QCD physics, especially its application in the study of quark-gluon-plasma （Q GP） formed in the relativistic heavy ion collision （RHIC）. This review is based on the talks given in several schools and programs for the phenomenologists working on nuclear physics and particle physics.